Dynamic & Static Finite Element Analysis of Non=Uniform Cross-Section Functionally Graded Composite Beam Subjected to Thermo-Mechanical Loading - Mathews, John George Mathews (2018)
Material improvement is quite vital as it is the key driver of the world we live in, because all areas of human undertakings in this developed world rely upon material advancement for their execution. The development of materials from solid material to composite depends on the constraint of one class of materials that requires the improvement of other classes of materials. For the need to have two materials consolidated, and to have the capacity to work and hold their properties after being subjected to harsh working environments, functionally graded material (FGM) was introduced. Although FGM was at first created for thermal barrier application, nonetheless the use of this imperative enhanced material has been expanded and used to unravel various issues in the applications of engineering. This research is conducted to reveal insight this imperative material. Chapter 1. An introduction of functionally graded material is presented, together with a brief historical background of FGM with my research approach. Chapter 2- Diverse sorts of functionally graded materials that are delivered today and their applications especially capitalizing on power energy sector. Chapter 3- Methodology process whereby modelling non-uniform two layered composite material beam. Onward simulation analysis of static and thermal-static loading whereby stage one results can be found in stage one report. Progressively, in stage two introducing FGM properties into the composite model with thermal-mechanical loading of static and dynamic. Chapter 4- Results and discussion by comparing composite (2 layer) beam with FGM beams defined. Chapter 5 - Project conclusion and future work.